Numerical analysis of laminar heat transfer in a channel with diamond-shaped baffles - Sripattanapipat, Somchai; Promvonge, Pongjet (My University, 2009)
Laminar periodic flow and heat transfer in a two dimensional horizontal channel with isothermal walls and with staggered diamond-shaped baffles is investigated numerically. The computations are based on the finite volume method, and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the hydraulic diameter of the channel ranging from 100 to 600. Effects of different baffle tip angles on heat transfer and pressure loss in the channel are studied and the results of the diamond baffle are also compared with those of the flat baffle. It is observed that apart from the rise of Reynolds number, the reduction of the baffle angle leads to an increase in the Nusselt number and friction factor. The computational results reveal that optimum thermal performance is at the baffle angle of 5° for baffle height and spacing of 0.5 and 1 times of the channel height, respectively. The thermal performance of the 5°-10°diamond baffle is found to be higher than that of the flat baffle for all Reynolds numbers used. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Baffle; Diamond baffle; Heat transfer; Laminar flow; Periodic channel flow